Quantification of Cooking Method Effect on COP Content in Meat Types Using Triple Quadrupole GC-MS/MS - Hashari S.Z.; Rahim A.A.; Meng G.Y.; Ramiah S.K. (NLM (Medline), 2024)
A diet containing cholesterol is an essential component of biological function; however, cholesterol oxidation products (COPs) remain a major public health concern. This study investigated the effects of cooking methods (boiling and frying) on the production levels of COPs in processed foods. Samples, as represented by minced beef, chicken sausages, and fish fillets, were subjected to different cooking methods followed by COP extraction using a saponification method. Then, six common COPs, 5α-cholest, α-epoxy, β-epoxy, 25-HC, triol, and 7-keto, were quantified by triple quadrupole gas chromatography-mass spectrometry (GS-MS/MS). A significantly high number of COPs were detected in minced meat, of which 7-keto and triol were detected as major oxidation products, followed by chicken sausages and fish fillets (p ≤ 0.05). Compared to boiling, frying generated significantly more COPs, specifically triol (0.001-0.004 mg/kg) and 7-keto (0.001-0.200 mg/kg), in all samples. Interestingly, cholesterol level was found to be slightly (but not significantly) decreased in heat-treated samples due to oxidation during cooking, producing a higher number of COPs. Notably, the fish fillets were found to produce the fewest COPs due to the presence of a low amount of cholesterol and unsaturated fatty acids. In conclusion, adapting boiling as a way of cooking and choosing the right type of meat could serve to reduce COPs in processed foods.